BCG vaccination: historical role, modern applications, and future perspectives in tuberculosis and beyond - Starshinova, Anna; Kudryavtsev, Igor; Rubinstein, Artem; Dovgalyuk, Irina; Kulpina, Anastasia; Churilov, Leonid P.; Kudlay, Dmitry (Frontiers in Pediatrics, 2025)
Tuberculosis (TB) remains a fatal disease primarily transmitted through airborne droplets, with children who are the most susceptible, particularly in the areas with poor tuberculosis control. The BCG vaccine, developed by Albert Calmette and Camille Guérin, has a history spanning a century. This vaccine has been implemented in numerous countries, significantly reducing child mortality in regions heavily affected by TB. In this review, we aim to revisit the vaccine's development and rollout, while also highlighting its current attributes and the successful application in the Russian Federation, where 90% of newborns receive the anti-tuberculosis vaccination. Due to that practice, only a few isolated cases of young children with generalized tuberculosis (about five to seven annually) are observed in Russia. Research on the BCG vaccine is ongoing, revealing significant genetic alterations in BCG strains that have evolved from the original variant. These genetic differences may contribute to variations in vaccine efficacy, making screening important to predict effectiveness. The BCG vaccine can initiate a localized mucosal immune response, offering, besides the anti-TB effect, some protection against infections involving mucous membranes, including salmonellosis, HIV, and acute viral respiratory infections. It is essential to investigate the role of BCG in various applications; however, this exploration should not detract from its main protective benefits against tuberculosis (TB). Future studies may provide evidence of the vaccine's safety and efficacy to support its use beyond TB prevention. While BCG vaccination does not lower the risk of infection with Mycobacterium tuberculosis, it does prevent the progression to the most severe clinical manifestations (such as miliary TB and tuberculous meningitis) caused by hematogenous spread of M.tuberculosis. The challenge of protecting HIV-infected children from TB remains urgent, especially in regions burdened with drug-resistant TB, highlighting the need for robust protective measures.